2022
DOI: 10.1007/s00198-022-06317-x
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal quantitative ultrasound is associated with all-cause and cardiovascular disease mortality independent of hip bone mineral density

Abstract: Osteoporosis has been linked with increased risk of cardiovascular disease previously. However, few studies have detailed bone and vascular information. In a prospective study of older women, we demonstrated heel quantitative ultrasound measures were associated with increased cardiovascular and all-cause mortality, independent of established cardiovascular risk factors. Introduction Osteoporosis and low bone mineral density (BMD) have been previously linked to cardiovascular disease (CVD) and mortality. Calcan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Some previous studies had reported a correlation between BMD or osteoporosis and the risk of all-cause mortality and CVD mortality.Research by Cai S showed that total femur (HR = 1.36, 95% CI = 1.07-1.73), femur neck (HR = 1.41, 95% CI = 1.11-1.78), intertrochanter (HR = 1.34, 95% CI = 1.05-1.72), and entire body (HR = 1.36, 95% CI = 1.09-1.69) osteoporotic participants had a higher risk of all-cause mortality compared with normal participants.However,the statistically signi cant L-shaped relationships were only identi ed for heart disease mortality with BMD increment within certain limits in the femur, whereas the remarkable relationships disappeared after BMD continued to increase [14].Other ndings from nationally representative cohorts also suggested that osteoporosis was associated with an increased risk of all-cause mortality(HR = 1.37, 95% CI = 1.11, 1.68), and this association was stronger in participants who were older and had a lower BMI.Similarly, non-signi cant results were observed for osteoporosis with CVD mortality in their study, the non-signi cant results might be due to the lower number of incident CVD, and cancer deaths, and short-time follow-up [15].Other studies had drawn some positive conclusions on the relationship between osteoporosis and cardiovascular disease risk.Irene's study included a total of 305,072 UK Biobank participants diagnosed with osteoporosis at baseline, the study concluded that men with osteoporosis had a higher mortality risk from CVD(HR = 1.68,95%CI = 1.19-2.37).However, women with osteoporosis only had a higher risk of incident CVD(HR = 1.24,95%CI = 1.97-1.44),and the risk of CVD mortality was not affected [16].Calcaneal quantitative ultrasound (QUS) was utilized to assess bone material properties, particularly in elderly women, and could also be used to diagnose osteoporosis.In a prospective study of aged women, A. K. Gebre found that quantitative ultrasound measurements of the calcaneus were independently associated with increased cardiovascular and all-cause mortality, independent of established cardiovascular risk factors.Reduction in broadband ultrasound attenuation (BUA) in the minimally and multi-variable adjusted model including cardiovascular risk factors increased relative hazard for all-cause mortality (HR = 1.15,95%CI = 1.06-1.261) and CVD mortality (HR = 1.20,95%CI = 1.04-1.38).Nonetheless, this observational study was limited to geriatric females only, and the results were not founded on the analysis of BMD values [17].In a similar study called the AA-DHS, vertebral BMD(vBMD) was analyzed in 675 African American men with T2DM and the results suggested that lower vBMD was associated with increased all-cause mortality, but regrettably, this study also showed that lower vBMD was not linked to other mortality risk factors, including subclinical atherosclerosis [18].…”
Section: Discussionmentioning
confidence: 92%
“…Some previous studies had reported a correlation between BMD or osteoporosis and the risk of all-cause mortality and CVD mortality.Research by Cai S showed that total femur (HR = 1.36, 95% CI = 1.07-1.73), femur neck (HR = 1.41, 95% CI = 1.11-1.78), intertrochanter (HR = 1.34, 95% CI = 1.05-1.72), and entire body (HR = 1.36, 95% CI = 1.09-1.69) osteoporotic participants had a higher risk of all-cause mortality compared with normal participants.However,the statistically signi cant L-shaped relationships were only identi ed for heart disease mortality with BMD increment within certain limits in the femur, whereas the remarkable relationships disappeared after BMD continued to increase [14].Other ndings from nationally representative cohorts also suggested that osteoporosis was associated with an increased risk of all-cause mortality(HR = 1.37, 95% CI = 1.11, 1.68), and this association was stronger in participants who were older and had a lower BMI.Similarly, non-signi cant results were observed for osteoporosis with CVD mortality in their study, the non-signi cant results might be due to the lower number of incident CVD, and cancer deaths, and short-time follow-up [15].Other studies had drawn some positive conclusions on the relationship between osteoporosis and cardiovascular disease risk.Irene's study included a total of 305,072 UK Biobank participants diagnosed with osteoporosis at baseline, the study concluded that men with osteoporosis had a higher mortality risk from CVD(HR = 1.68,95%CI = 1.19-2.37).However, women with osteoporosis only had a higher risk of incident CVD(HR = 1.24,95%CI = 1.97-1.44),and the risk of CVD mortality was not affected [16].Calcaneal quantitative ultrasound (QUS) was utilized to assess bone material properties, particularly in elderly women, and could also be used to diagnose osteoporosis.In a prospective study of aged women, A. K. Gebre found that quantitative ultrasound measurements of the calcaneus were independently associated with increased cardiovascular and all-cause mortality, independent of established cardiovascular risk factors.Reduction in broadband ultrasound attenuation (BUA) in the minimally and multi-variable adjusted model including cardiovascular risk factors increased relative hazard for all-cause mortality (HR = 1.15,95%CI = 1.06-1.261) and CVD mortality (HR = 1.20,95%CI = 1.04-1.38).Nonetheless, this observational study was limited to geriatric females only, and the results were not founded on the analysis of BMD values [17].In a similar study called the AA-DHS, vertebral BMD(vBMD) was analyzed in 675 African American men with T2DM and the results suggested that lower vBMD was associated with increased all-cause mortality, but regrettably, this study also showed that lower vBMD was not linked to other mortality risk factors, including subclinical atherosclerosis [18].…”
Section: Discussionmentioning
confidence: 92%
“…Osteoporosis is an important risk factor for accidents, disability, and death (51). Therefore, this finding is of great significance to public health.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, a larger sample size was used, and a more comprehensive assessment was conducted in this study, which not only proved a negative causal relationship between UC and forearms BMD and body BMD but also found a negative causal relationship between IBD and body BMD at the age of 45–60 years. Osteoporosis is an important risk factor for accidents, disability, and death ( 51 ). Therefore, this finding is of great significance to public health.…”
Section: Discussionmentioning
confidence: 99%
“…The average measurement of broadband ultrasound attenuation, speed of sound, and stiffness index were recorded as detailed. [ 23 ] Total hip and femoral neck BMD of subjects was measured by DXA (Hologic Acclaim 4500A fan‐beam densitometer; Hologic Corp, Waltham, MA, USA). The coefficient of variation at the total hip was 1.2% in our laboratory.…”
Section: Methodsmentioning
confidence: 99%